2019
DOI: 10.1007/s10815-019-01627-2
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid (TUDCA) enhanced intracytoplasmic sperm injection (ICSI) embryo developmental competence by ameliorating endoplasmic reticulum (ER) stress and inhibiting apoptosis

Abstract: Purpose The objective of this study was to examine the effect of tauroursodeoxycholic acid (TUDCA) on intracytoplasmic sperm injection (ICSI) embryos by evaluating endoplasmic reticulum (ER) stress, apoptosis, and embryo developmental competence in vitro and in vivo. Methods ER stress-associated genes and apoptosis-associated genes were measured and apoptosis index was analyzed. Embryo developmental competence was assessed in vitro and in vivo via the inner cell mass (ICM)/trophectoderm (TE) index, pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In this study, the secondary bile acids deoxycholic acid and taurochenodeoxycholic acid were increased in DF 1.75 gilts compared with DF 1.0 gilts. Tauroursodeoxycholic acid was shown to facilitate DNA damage repair and improve early embryo development in pigs [ 55 ] and other mammals [ 56 ]. Additionally, DF intake also altered levels of other metabolites, including spermidine [ 57 ], 4-aminobenzoic acid [ 58 ] and ibuprofen [ 59 ] that are known to influence oocyte quality or reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the secondary bile acids deoxycholic acid and taurochenodeoxycholic acid were increased in DF 1.75 gilts compared with DF 1.0 gilts. Tauroursodeoxycholic acid was shown to facilitate DNA damage repair and improve early embryo development in pigs [ 55 ] and other mammals [ 56 ]. Additionally, DF intake also altered levels of other metabolites, including spermidine [ 57 ], 4-aminobenzoic acid [ 58 ] and ibuprofen [ 59 ] that are known to influence oocyte quality or reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…But, limited by the biological characteristics of SVZ, we only detected the ER stress and microglia in SGZ, which is a deficiency in our work. Another deficiency was the selectivity and specifically of TUDCA in inhibitory on ER stress [48][49][50][51] . Collectively, those results suggested that the increased ER stress in microglia might be a possible pathway for PQ-induced neuroinflammation and NSC impairment.…”
Section: Discussionmentioning
confidence: 99%